Answer:
5x^4 -37x^3 -6x^2 +41x -6
Step-by-step explanation:
We simplify this expression by removing parentheses and combining like terms. Parentheses are removed using the distributive property.
<h3>Form the product</h3>
The product of the final pair of polynomials in parentheses is ...
(-4x^3 +5x -1)(2x -7) = (-4x^3 +5x -1)(2x) +(-4x^3 +5x -1)(-7)
= -8x^4 +10x^2 -2x +28x^3 -35x +7
= -8x^4 +28x^3 +10x^2 -37x +7
<h3>Combine with remaining sums</h3>
= (5x^4 -9x^3 +7x -1) + (-8x^4 +4x^2 -3x +2) - (-8x^4 +28x^3 +10x^2 -37x +7)
= (5 -8 -(-8))x^4 +(-9 -28)x^3 +(4 -10)x^2 +(7 -3 -(-37))x +(-1 +2 -7)
= 5x^4 -37x^3 -6x^2 +41x -6